2008
DOI: 10.1021/nl8012456
|View full text |Cite
|
Sign up to set email alerts
|

Probing Hot Electron Flow Generated on Pt Nanoparticles with Au/TiO2Schottky Diodes during Catalytic CO Oxidation

Abstract: Hot electron flow generated on colloid platinum nanoparticles during exothermic catalytic carbon monoxide oxidation was directly detected with Au/TiO 2 diodes.Although Au/TiO 2 diodes are not catalytically active, platinum nanoparticles on Au/TiO 2 exhibit both chemicurrent and catalytic turnover rate. Hot electrons are generated on the surface of the metal nanoparticles and go over the Schottky energy barrier between Au and TiO 2 . The continuous Au layer ensures that the metal nanoparticles are electrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 31 publications
5
130
1
5
Order By: Relevance
“…They proposed a possible photocatalytic mechanism: under visible light irradiation the surface plasmon band of Au nanoparticles will be excited and will inject electrons (−) to the conduction band of the TiO 2 , which facilitates water reduction to hydrogen, and the holes (+) remaining on Au nanoparticles will be responsible for the oxidation of adsorbed CO. Furthermore, "hot-electron flow" can be formed between metal-oxide interfaces during exothermic chemical processes, and the "hot-electron flow" plays a key role in determining the catalytic activity of CO oxidation [46,[56][57][58]. Accordingly, correlating traditional and photocatalytic WGS reaction mechanisms with the optoelectronic properties, we try to understand the WGS pathway from the view of electron flow processes, as shown in Figure 10.…”
Section: Proposed Electron Flow Processmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed a possible photocatalytic mechanism: under visible light irradiation the surface plasmon band of Au nanoparticles will be excited and will inject electrons (−) to the conduction band of the TiO 2 , which facilitates water reduction to hydrogen, and the holes (+) remaining on Au nanoparticles will be responsible for the oxidation of adsorbed CO. Furthermore, "hot-electron flow" can be formed between metal-oxide interfaces during exothermic chemical processes, and the "hot-electron flow" plays a key role in determining the catalytic activity of CO oxidation [46,[56][57][58]. Accordingly, correlating traditional and photocatalytic WGS reaction mechanisms with the optoelectronic properties, we try to understand the WGS pathway from the view of electron flow processes, as shown in Figure 10.…”
Section: Proposed Electron Flow Processmentioning
confidence: 99%
“…As shown in Figure 10a, since the work function of metal Au (Φ m = 4.8 eV) is smaller than that of semiconductor TiO 2 (Φ s = 5.1 eV) [70], the electrons can diffuse from the metal into the semiconductor when the two phases are in contact [71,72]. This electron transfer was called "hot-electron flow" [56,57,[73][74][75] or "chemicurrent" [76][77][78], which usually happened in exothermic catalytic reactions [56,57,[73][74][75] and low-energy reactions [74] or even nonthermal directions [75]. For example, it has been reported that electron excitation was also involved in atomic/molecular adsorption processes [73,77,78].…”
Section: Proposed Electron Flow Processmentioning
confidence: 99%
“…This generates a hot electron, which, if the distance of travel to a Schottky interface is less than the mean free path of the electron, can cross the barrier and end up in the conduction band of the oxide (allowing a current to be measured). This has been done with both Pt films [84][85][86][87][88] and colloidal Pt nanoparticles on a Au/TiO 2 nanodiode, [89,90] the latter is depicted in Figure 6. higher potential than in Au, causing current to flow so a "chemicurrent" can be measured…”
Section: The Oxide Metal Interfacementioning
confidence: 99%
“…[8,33,101] [40,41,107] Wir detektierten einen Strom "heißer" Elektronen mithilfe einer Schottky-Diode. [38,39,106,108] Werden Metallpartikel [59] oder ein Film [109] mit Durchmessern bzw. einer Dicke ähnlich der mittleren freien Weglänge für Elektronen (ca.…”
Section: Ladungstransportunclassified